Muck 'n' molecules : organic geochemical methods for detecting ancient manuring - Bull, I. D.; Simpson, I. A.; Bergen, P. F. van; Evershed, R. P.
The detection of manuring in antiquity can provide important information concerning the agricultural and waste disposal practices of ancient communities. Faecal biomarkers provide a reliable and highly diagnostic method for detecting ancient faecal inputs to soils irrespective of any morphological remnants of manuring.